Clostridium difficile. (October 2017) - Planche, Tim; Karunaharan, Natasha
Abstract: Clostridium difficile causes a potentially life-threatening diarrhoea, which is acquired predominantly in hospitals. The incidence of infections caused by this organism has increased markedly over the past 20 years, although the incidence has fallen in the UK since a peak about 10 years ago. Suspicion of the condition should be high, and cases should be managed appropriately. Initiation of early treatment and rapid confirmation of diagnosis are critical to the management of C. difficile infection (CDI). CDI should be treated as a new diagnosis and urgently assessed. After severity has been assessed, appropriate treatment should be started. Risk factors for CDI include age, immune suppression and use of broad-spectrum antibiotic therapy. Infection control measures to reduce CDI rates should be an integral part of the management of all hospitals. These measures include isolation of cases, hand-washing, environmental cleaning and antibiotic stewardship.